It Is Impossible to Remain Silent : Reflections on Fate and Memory in Buchenwald - Semprún, Jorge; Wiesel, Elie, 1928-2016 (Book collections on Project MUSE., 2020)
"On March 1, 1995, at the time of the fiftieth anniversary of the liberation of the Nazi concentration camps, ARTE (a French-German state-funded television network) proposed an encounter between two highly regarded figures of our time: Elie Wiesel and Jorge Semprún. These two men, whose destinies were unparalleled, probably had crossed paths, without ever meeting, in the Nazi concentration camp Buchenwald in 1945. This short book is the entire transcription of their recorded conversation. During World War II, Buchenwald was the center of a major network of sub-camps and an important source of forced labor. The camp interned mostly German political inmates, but held 10,000 Jews, Roma, Sinti, Jehovah's Witnesses, and German military deserters. In these poignant pages, Wiesel and Semprún discuss the human condition under catastrophic circumstances. They review the categories of inmates at Buchenwald and agree on the tragic reason for the fate of the victims of Nazism--as well as why this fate was ignored for so long after the end of the war. Both men offer riveting testimony and vibrant homage to the Jewish victims of the Holocaust. This book could not be more timely for its confrontation with ultra-nationalism and antisemitism"--